Cardiovascular and autonomic activity responses after Active Cycle of Breathing Technique (ACBT) in healthy thais - Wattanapanyawech, Jirawat; Namahut, Titaree; Parinyanont, Thansuta; Ekudomlert, Warin (Health Science, Science and Technology Reviews, 2021)
Currently, patients with respiratory conditions often had hypertension. The active cyclic breathing therapy (ACBT) technique is an effective technique for secretion clearance. Aim of this study was to clarify the physiological responses of the cardiovascular and autonomic nervous system activity after ACBT program. For safety reasons, it is necessary to understand the physiological response after ACBT program. Twenty subjects performed ACBT for 12 minutes and assessed cardiovascular response and autonomic activity before and after ACBT program. The results showed that ACBT affects systolic blood pressure (p <0.01), heart rate, oxygen saturation, and rate perceived exertion (p <0.05) was significantly increased. Moreover, significantly increased low frequency (LF) (p <0.05), and significantly reduced in high frequency (HF) and LF / HF. ratio (p <0.05) were observed after ACBT program. ACBT affects increased sympathetic activity leading to increased cardiovascular response. Treating respiratory patients with cardiovascular disease or abnormal autonomic activity with ACBT program should be careful.